Music Education and the Neoliberal Turn in Aotearoa New Zealand - McPhail G; McNeill J (The MayDay Group, 2021)
In this paper we explore the adoption of a neoliberal turn in New Zealand’s education system and its consequences, focusing particularly on secondary school music education. In the 1980s, New Zealand was one of the first states in the Western world to implement comprehensive neoliberal economic policies. Some 35 years later, education in New Zealand is situated in a highly devolved institutional framework that privileges neoliberal objectives. This article outlines the genesis of this socio-political context and the downstream effects of this environment on the secondary school music curriculum. Our central question is this: What have been the results of the “New Zealand Experiment” in terms of the type of music curriculum students now experience? The deeper problematic of the paper, however, concerns the fragmentation and instrumentalization of knowledge. On balance, we conclude that effects of the neoliberal turn within education in New Zealand may have been more detrimental than beneficial, as these agendas have encouraged a break with past more liberal and humanistic aims for education. However, we also argue that the changes have not been the product of any systematic project but rather the result of a confluence of complex and stratified causal mechanisms at work in the socio-political world.
Keywords: 1302 Curriculum and Pedagogy